Growth, bone mass, and vitamin D status of Chinese adolescent girls 3 y after withdrawal of milk supplementation1–3 - Kun, Zhu; Qian, Zhang; Leng, Huat Foo (American Society for Nutrition, 2006)
Background: A 2-y school milk intervention trial showed that 330 mL of a dietary milk supplement (fortified with calcium alone or with both calcium and vitamin D) enhanced the growth and bone mineral accretion of Chinese girls aged 10 y at baseline. Girls who received milk fortified with both calcium and vitamin D also had better vitamin D status than did girls who received nothing or girls who received milk fortified only with calcium. Objective: The aim was to evaluate whether these effects were sustained 3 y after supplement withdrawal. Design: Anthropometric measures and dietary intake were reassessed in 501 of the 698 girls whose data had been studied at the end of the intervention. As in the intervention phase, total-body bone mineral content and bone mineral density and serum 25-hydroxyvitamin D concentrations were measured in half of these subjects. Results: At follow-up,99%of girls had reached menarche, at a mean (SD) menarcheal age of 12.11.1 y. No significant differences in the timing of menarche were observed between the 3 groups (P 0.6). No significant differences in the changes of total-body bone mineral content and bone mineral density since baseline were observed between the groups. The group receiving calcium-fortified milk had significantly greater gains in sitting height (0.9 0.3%; P 0.02) than did the control group. The group that received calcium- and vitamin D–fortified milk had 17.16.7% lower serum 25-hydroxyvitaminDconcentrations than did the control group (P 0.04), but the difference was attenuated by additional adjustment for physical activity level (14.2 6.7%; P 0.08). Conclusion: Milk supplementation during early puberty does not have long-lasting effects on bone mineral accretion.